A comparative study between two techniques of laparoscopic orchiopexy for intra-abdominal testis - Bawazir, Osama; Maghrabi, Abdulrahman (Indian journal of urology, 2021)
Introduction: Several techniques have been described for laparoscopic orchidopexy in patients with intra-abdominal testes. We aimed to report our experience with the staged laparoscopic traction orchiopexy (Shehata technique) and to compare it to the Fowler-Stephens orchidopexy (FSLO). Methods: We conducted a retrospective cohort study at two pediatric surgery departments from 2017 to 2020. Fifty-six patients underwent laparoscopic exploration and the testis was intra-abdominal in 41 of them. Patients with vanished testis or those who underwent open orchidopexy or vessel-intact laparoscopic orchidopexy were excluded. Those who underwent FSLO (n = 18), or Shehata laparoscopic orchidopexy (n = 11) were compared. Results: Preoperative data were comparable between both the groups. FSLO had a significantly shorter first-stage operative time (34.61 ± 6.43 vs. 58 ± 9.39 min, P < 0.001), with no difference in the second stage. There was no difference in the initial position of the testes between both the techniques. The testis dropped from the fixation position in three patients in the Shehata group (27.27%), and consequently, the cord did not increase in length by the second stage, and these testes barely reached the scrotum. At 12 months' follow-up, the testes' size, position, and consistency were comparable between the two groups. Conclusion: Staged laparoscopic traction orchidopexy is feasible for the management of intra-abdominal testes, especially in the low-lying testes.